دور الميكانيزمات الداخلية لحوكمة الشركات في تحسين الأداء الإجتماعي في المؤسسات الإقتصادية الجزائرية -دراسة حالة شركة Cilas للإسمنت بجمورة- بسكرة – - سكر فتيحة; عديسة شهرة (جامعة الوادي univerciti of eloued, 2024)
The study aimed to highlight the role of internal mechanisms of corporate governance in improving social performance in CILAS Cement Company in Jamourah Biskra, To achieve this goal, a questionnaire was designed that included a set of questions covering the study axes, as it was distributed to a random sample that included heads of departments, internal auditors, and employees of the company. By analyzing the results of the questionnaire through the 22 Spss program, the study reached a number of results, the most important of which is the presence of an impact of the mechanisms of the board of directors and disclosure on social performance, while the internal audit mechanism had no impact on the social performance of the company under study.
The role of internal mechanisms of corporate governance in improving social performance in Algrtian economic institutions- Case study of CILAS Cement Company in Jamora - Biskra -
Keywords: حوكمة الشركات; الميكانيزمات الداخلية; الأداء الإجتماعي; المؤسسات الإقتصادية; شركة سيلاس للإسمنت; corporate governance; internal mechanisms; social performance; Economic institutions